(untitled) (Progressive Agriculture, 2013)
The main purpose of the research was to identify factors responsible for yield gap in wheat production. Eighteen (18) experiments were conducted in two major wheat growing districts Rangpur and Dinajpur in two consecutive years. The selected varieties for the conducted research were Prodip, Satabdi and Sourav. All the experiments were established in farmers fields providing all recommendations for wheat production. It was observed that yield gap varied with the variety and farmers to farmers and location to location. The overall yield gap of Prodip was the highest (18.43 percent) followed by Sourav (18.15 percent) and Satabdi (17.45 percent). Yield gaps of all the wheat varieties under study were higher in Rangpur site than Dinajpur site. The practice gap was the highest in gypsum application (69 percent) followed by boron (67 percent), sowing time (40 percent). Practice gaps in the application of MoP, TSP and irrigation were almost equal, 40 percent, 37 percent, and 36 percent respectively. Late sowing, non use of dolomite and micro nutrients (zinc and boron) in wheat yield with sub-optimal doses of phosphatic and potash fertilizers were the main reasons for yield gap. Adoption of short duration T. aman variety and optimal doses of chemical fertilizers with micro nutrients in wheat field could minimize this gap to a greater extent. Preventive measures against bird attack after sowing of seeds for optimum plant population would have impact in narrow down this yield gap as well. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16620 Progress. Agric. 23(1 & 2): 91 99, 2012